Kualitas Hidup pada Anak dengan Kanker - Ikeu Nurhidayah; Sri Hendrawati; Henny S. Mediani; Fanny Adistie (Jurnal Keperawatan Padjadjaran, 2016)
Kanker anak merupakan penyakit yang memerlukan pengobatan dan perawatan berkelanjutan. Pengobatan kemoterapi yang berkelanjutan pada anak dengan kanker, selain memiliki efek terapeutik juga menyebabkan berbagai efek samping. Hal ini dapat berdampak terhadap kualitas hidup anak, meliputi fungsi fisik, emosi, sosial, psikologis, sekolah, dan kognitif. Tujuan penelitian ini untuk mengidentifikasi kualitas hidup pada anak dengan kanker. Penelitian ini menggunakan mixed method dengan strategi eksplanatoris sekuensial. Sampel penelitian kuantitatif dengan 60 responden. Kualitas hidup pada anak diukur dengan menggunakan instrumen PedsQoL Generic 4.0 dan PedsQoL Cancer Module 3.0. Analisis data dilakukan menggunakan nilai mean. Penelitian kualitatif menggunakan 10 partisipan dan pengumpulan data dengan pedoman wawancara. Analisis data menerapkan teknik analysis interactive model dengan tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini dilaksanakan di RSUP Dr. Hasan Sadikin Bandung. Hasil penelitian menunjukkan 32 orang (53,3%) anak kanker memiliki kualitas hidup buruk, dengan nilai terendah pada fungsi sekolah dan kekhawatiran anak dalam menghadapi pengobatan dan penyakit.Kualitas hidup yang buruk ini berpengaruh terhadap fungsi fisik, emosi, sosial, psikologis, sekolah, dan kognitif sehingga tumbuh kembang anakpun terganggu. Salah satu upaya untuk meningkatkan kualitas hidup pada anak dengan menyediakan kesempatan bagi anak untuk tetap belajar dan saling berinteraksi dan dukungan dari perawat.Kata kunci: Anak, kanker, kualitas hidup. Quality of Life of Children Living with CancerAbstractCancer in children is an illness that needs continuous medication and treatment so that it has to be managed with high quality care. Continuous chemotherapy treatment in children with cancer, besides giving therapeutic effect, it also causes various side effects. These side effects could have negative effect for quality of life of the children, including physical, emotional, social, psychological, school, and cognitive functions. The aim of this study was to identify quality of life of children living with cancer. This study used mixed method design with sequential explanatory strategy. The quantitative study recruited 60 samples of children living with cancer. The quality of life of the children was measured using PedsQol Generic 4.0 and PedsQoL Cancer Module 3.0. Data were analyzed using mean score. The qualitative study recruited 10 participants and the data were collected using semi-structured interview. Qualitative data analysis used interactive analysis model which consisted data collection, data reduction, data presentation, and conclusion phases. Both of the studies were conducted at Dr. Hasan Sadikin Hospital Bandung. The results showed that based on PedsQol Generic 4.0, most of the children (53.3%) has low quality of life, with the school function as the lowest score. Based on PedQoL Cancer Module 3.0, most of children (61.7%) also has low quality of life, particularly in children’s worriedness aspect when dealing with treatment and their illness which has lowest score. This low quality of life would have negative impact towards children’s physical, emotional, social, psychological, school and cognitive function, so that it disturbed the children’s growth and development. One of efforts that can be done is to provide opportunities for children to continue studying and interaction in hospital, as well as an additional schedule for psychology therapies to help children overcome the negative emotion during their treatment.Keywords: Cancer, children, quality of life.